Factores externos en la percepción de las consonantes silábicas y la schwa en inglés - Arboleda Guirao, Inmaculada de Jesús; Rodríguez Gómez, Patricia (Huarte de San Juan. Filología y Didáctica de la Lengua, 2014)
This paper deals with the perception of English syllabic consonants vs. schwa finally in a word at discourse level. The fact that these phonemes are constantly present in speech (Trask 1996) and the lack of studies which focus on their perception (see, however, van Bergem 1995) make further exploration eligible. The informants for this study were 80 non-rhotic native newsreaders (40 males and 40 females) taken from the BBC Learning English website (2009). Three female listeners not knowledgeable about the purposes of the study had to decide whether they perceived a schwa or a syllabic consonant in 800 words. The data were analysed with the help of SPSS. The statistical procedures used were chi-square tests and Kendall’s coefficients of concordance. Results revealed that word emphasis is statistically associated with the perception of syllabic consonants and schwa and the referees employ different assessment criteria in terms of word position.